2012
DOI: 10.2147/jmdh.s27841
|View full text |Cite
|
Sign up to set email alerts
|

Health research barriers in the faculties of two medical institutions in India

Abstract: BackgroundHealth policy formation refers to the design of a conceptual framework to find possibilities, facilitate feasibilities, and identify strong and weak points, as well as insufficiencies, by research. Doing research should clarify qualities and standards for policy and decision-making to enable the success of development of health care in a country. Evaluation of the impact of health interventions is particularly poorly represented in public health research. This study attempted to identify barriers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Literature review in PubMed brings forth only a few articles that emphasize the gaps in research related knowledge. [ 2 15 16 ] Further studies are necessary to address these core issues and resolve them. Challenges of support: The right support leads to a better research environment which in turn leads to a better support system resulting in a positive and constructive cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature review in PubMed brings forth only a few articles that emphasize the gaps in research related knowledge. [ 2 15 16 ] Further studies are necessary to address these core issues and resolve them. Challenges of support: The right support leads to a better research environment which in turn leads to a better support system resulting in a positive and constructive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review in PubMed brings forth only a few articles that emphasize the gaps in research related knowledge. [ 2 15 16 ] Further studies are necessary to address these core issues and resolve them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Lack of motivation 30,38 -Need for leadership 29,30,34,38 -Lack of interest by policy-makers 28,30,32,34 -Identify young leaders (e.g., researchers, scientists, doctors, trialists) who are committed to research in clinical trials and support professional development. -Existing senior leaders should implement a structured mentoring regimen and a clear succession plan to facilitate the development of the younger generation.…”
Section: Individualmentioning
confidence: 99%
“…At an individual level there is limited access to research training and exposure during early career years. [28][29][30][31]37,38 In addition, limited access to leadership and mentorship was highlighted as a limiting factor to engage in research. 29,30,34,38 Some studies reported absence of suitable research infrastructure leading to the lack of scientific atmosphere (e.g., lack of collaboration, poor communication among stakeholders, and low remuneration for research activities).…”
Section: Population and Individual Levelmentioning
confidence: 99%